HEALTH RECORDS AND INFORMATION TECHNOLOGY IN SUPPORT OF EXCHANGE OF HEALTH INFORMATION - Jordan Deliversky (Peytchinski Publishing, 2017)
The exchange of health information in conditions directly related to electronic environment is referred as health information technology. Usually the protection of personal health related data is comprised of various elements such as ways of information usage and access to sensitive health information. The protection of individually identifiable health information is possible with combination of measures. Protective measures include administrative, technical and physical elements. Through such protective measures is possible to ensure confidentiality, integrity and availability of the information, while at the same time could be guaranteed the prevention of unauthorized access. Sensitive records usually contain personal health information. Personal medical data requires high level of protection, as its content includes medical condition or diagnosis, where unauthorized access could have negative impact on one's personal and professional life.